2015
DOI: 10.1016/j.cct.2015.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Family Access to a Dentist Study (FADS): A multi-center randomized controlled trial

Abstract: Introduction Many low-income parent/caregivers do not understand the importance of cavity-free primary (baby) teeth and the chronic nature of dental caries (tooth decay). As a consequence, dental preventive and treatment utilization is low even when children are screened in schools and referred for care. This study aims to test a referral letter and Dental Information Guide (DIG) designed using the Common-Sense Model of Self-Regulation (CSM) framework to improve caregivers’ illness perception of dental caries … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…Although the recognition of poor dental health in children is important, it is unclear how this perception is processed in the parents. Further research is required to investigate the dynamics of their coping mechanisms (Nelson et al, ). The parents' recognition of their children's oral health problems is a basic step toward the search for treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the recognition of poor dental health in children is important, it is unclear how this perception is processed in the parents. Further research is required to investigate the dynamics of their coping mechanisms (Nelson et al, ). The parents' recognition of their children's oral health problems is a basic step toward the search for treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Although the recognition of poor dental health in T A B L E 5 Crude and adjusted odds ratios of the mixed-effects logistic regression models of maternal perception of a child's oral health and sociodemographic, dental caries, and molar incisor hypomineralization children is important, it is unclear how this perception is processed in the parents. Further research is required to investigate the dynamics of their coping mechanisms (Nelson et al, 2015). The parents' recognition of their children's oral health problems is a basic step toward the search for treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Our secondary hypothesis was that the increase in child dental care utilization would be through the primary mediating effect of changes in caregiver illness representation/perception by influencing behavioral intention, after controlling for relevant child and caregiver socio-demographic characteristics. The design and details of this study has been previously reported [26]. …”
Section: Methodsmentioning
confidence: 99%
“…While these results are encouraging, there remains an important population of students who failed to access restorative care despite these services and for whom additional case management or access to school‐based and community‐based restorative dental care may be needed. Understanding how to improve the effectiveness of screening and referral programs and address barriers to accessing a dental home , are critical to addressing the substantial unmet oral health needs of low‐income children.…”
Section: Discussionmentioning
confidence: 99%
“…Studies suggests that education alone is not likely to substantially reduce caries . Various behavior change theories have been applied to oral health , but it remains unknown how to most effectively target and successfully change the drivers of oral health behaviors. Achieving a deeper understanding of this issue will be critical to reducing the overall burden of disease among vulnerable children.…”
Section: Discussionmentioning
confidence: 99%